Bioethanol Characteristics of Musa Paradisiaca Artocarpus Peel - Muhaji Muhaji; I Made Arsana; Belina Yunitasari (Institute of Research and Community Outreach, Petra Christian University, 2025)
The objectives of this research are to analyze the chemical and physical properties of bioethanol as well as production costs. Data were collected using experimental methods. The raw material, musa paradisiaca artocarpus Peel, was processed through saccharification, fermentation, and distillation. The experiment used 500 grams of peel, 25 grams of yeast, and 20 grams of urea, with fermentation lasting four days and five-stage distillation conducted at 78°C, utilizing pumice stone adsorbent with a 70-mesh size. Chemical properties of the bioethanol were tested using ASTM standards: ethanol content (D5501), methanol content (D5501), water content (D1744), copper (D1688), acidity (D1613), chloride (D512), sulfur (D2622), and gum content (D381). Physical properties were tested using ASTM standards: density (D1298), kinematic viscosity (D445), flash point (D93), heating value (D240), boil point (D2892), pH (D6423), and octane number (D976). The results of the chemical property analysis showed that the bioethanol contained 99.65%-v ethanol, 0.02% methanol, 0.01% water, 0.02 mg/kg copper, 19 mg/l acidity, 16.75 mg/l chloride, 0.01 mg/l sulfur, and 1.02 mg/100 ml gum. The physical property analysis results revealed a density of 0.787 g/cm³, kinematic viscosity of 1.28 cSt, flash point of 18°C, boiling point of 78°C, heating value of 6985 kcal/kg, pH of 6.9, and an octane number of 107. Production costs for producing 1 litre bioethanol from musa paradisiaca artocarpus Peel with 99.65%-v ethanol content costs Rp.47,782,. Overall, this bioethanol offers excellent performance and environmental benefits, making it a viable alternative to as a substitute or a mixture of gasoline fuels.